The media trial of Jacob Zuma: ethical journalism in the new South Africa - Utting, Lauren Elise (My University, 2011)
This research report focuses on the ‘media trial’ claim of current South African president Jacob Zuma and his allegation, after the dropping of the charges by the National Prosecuting Authority that he was unfairly ‘tried by the media’. I will argue that the media treatment Jacob Zuma received in the run up to the 2009 general election was ethically and reasonably in line with acceptable journalistic practice. I will argue this claim by presenting a detailed analysis of the ethical norms and considerations that govern responsible journalism and then make practical application of these to the two hard cases that Jacob Zuma brought before the courts in support of his claim. The two cases concern The Guardian newspaper and Jonathon Shapiro (Zapiro), political cartoonist to the Mail and Guardian newspaper. My analysis will show that both The Guardian and Zapiro were not guilty of unfair media treatment against Zuma